Providence, July 26, 1779. Sir ; By the annexed vote of the town of Providence, you will perceive the anxious desire they possess of having the purposes therein expressed carried into execution - Bowen, Jabez, 1739-1815 (Printed by John Carter, 1779)
Circular letter from the Providence Committee of Correspondence, followed by a resolve of the town of Providence, July 23, 1779, calling for a convention of delegates to be held at East-Greenwich on the 2d Tuesday of August in order to agree upon measures "for preventing any further depreciation of the Continental currency and for reinstating and supporting the credit thereof" pursuant to the recommendation of Congress in their address of May 26, 1779.